Severidades. Lecturas MR 107 floración [Conjunto de datos] - Crociara, Clara Sonia; Valetti, Lucio; Iglesias, Juliana; Pastor, Silvina Estela (2025)
Supplementary data set to the article "Unlocking Hidden Sources of Resistance to Ascochyta Blight in Moderately Resistant Chickpea Genotypes."